IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI MEDIA FILM DALAM PEMBELAJARAN AKIDAH AKHLAK: Penelitian Deskriptif Kualitatif di Kelas VIII MTs. Miftahul ‘Ulum Dan MTs. Asy-Syifa Kecamatan Cipatat Kabupaten Bandung Barat - Arip Muhazir; Badruzzaman M. Yunus; Asep A. Fathurrohman; Wati Karmila (STAI Pelabuhan Ratu, 2021)
This research is motivated by the rapid flow of information, entertainment and social media affecting the lifestyle and character formation of students. The low motivation of educators to improve competence and skills in the mastery of technology as a medium of learning is also one of the causes of this problem. This research aims to explain the implementation of character education through film media in moral learning. This research is a qualitative description, using a case study approach in class VIII MTs. Miftahul 'Ulum and MTs. Asy-Syifa District Cipatat West Bandung Regency. The author uses observation methods, interviews/ interviews, documentation. Data analysis techniques using data reduction techniques, data presentation, and conclusions The results of this study, illustrate that the utilization of learning using multimedia becomes a solution in improving the quality of learning carried out in the classroom, and becomes an alternative to overcoming the limitations of teaching opportunities implemented by educators. The function of multimedia learning as a source of learning is channeling, presenter, liaison, and others. Multimedia learning as a learning link is able to streamline the communication process so that the desired goal is achieved by changes in student behavior